Conjunctival Biopsy as a First Choice to Confirm a Diagnosis of Sarcoidosis - Korkmaz Ekren, Pervin; Mogulkoc, Nesrin; Toreyin, Zehra Nur; Egrilmez, Sait; Veral, Ali; Akalın, Taner; Bacakoglu, Feza (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Sarcoidosis is a granulomatous systemic disease of unknown aetiology. The diagnosis needs histological confirmation of the presence of non-caseating granulomata. One option is a conjunctival biopsy. The aims of this study were to evaluate conjunctival biopsy for the diagnosis of sarcoidosis with respect to its sensitivity and to assess its cost effectiveness by comparison with other histopathological diagnostic procedures. Methods: Patients were identified from the database of the Interstitial Lung Disease Clinic (ILDC) of the Chest Department of Ege University Hospital from May 2008 to June 2014. The patients who had biopsy procedures performed for the definitive diagnosis of sarcoidosis were assessed. Their diagnostic procedures and the cost of procedures were recorded. The cost per positive result for each procedure was calculated. Results: In total, 280 patients were followed up with a diagnosis of sarcoidosis, of whom 174 had histological confirmation; these constitute the study population. There were 127 females and 47 males with a median age of 46 years (range 14-78 years). Forty three patients had conjunctival biopsy and we could establish a diagnosis in 54% of these by means of conjunctival biopsy. Moreover, we showed that this biopsy can provide positive result for sarcoidosis patients who lack abnormal eye findings. Additionally, it is cost effective approach and without complications. Conclusion: This study re-asserts the value of conjunctival biopsy, which was described in the past but is not commonly used nowadays. In the presence of suggestive clinic and radiologic findings, we recommend conjunctival biopsy as the first choice for the histopathological confirmation of sarcoidosis.